Transition from Gesture and Gesture Nomination to Phraseology - E. R. Ioanesyan (Научный диалог)
Based on the material of several languages, semantic transitions from gestural nominations to gestural phraseological units, as well as the development of figurative meanings of gestural units are considered. The subject of the study is emblems — communicative gestures containing information that a person intentionally conveys to the addressee, and symptomatic gestures — gestures that express the emotional state of the gesticulator. The study showed that the transition from gestural nomination to gestural phraseology is often accompanied by a change in the actant structure of the original unit. One of the signs of the transition from gesture to gesture phraseology is the generalization of the situation — the generalization of one of the actants of the situation, which is expressed by the presence in the sentence of quantifier units that form universal noun phrases with nouns. Idiomatization of gestural units in different languages has both similarities and differences: differences in the meaning of phraseological units built on the basis of gestural units of the same semantics, or differences in the derivational potential of similar gestural units in different languages. The relevance of the study is due to the fact that gestures play a huge role in oral communication, and the fact that it was carried out in line with such areas as the construction of explanatory models of language and semantic typology.